Políticas públicas educacionais: a efetivação da EAD na Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present work has as a theme the study of the public policy of Distance Education, as well as the institutional policy of deployment of courses in distance mode at the Universidade Federal do Pampa - UNIPAMPA, as well as the study of its applicability and the academic streams. The choice of this theme arose from observations made in my professional practice during the implementation of the course of geography - Bachelor EaD-UNIPAMPA-UAB. Considering the growth of enrolment EaD at national in scope, and the efforts of the unipampa in contributing to its growth and institutionalization in university, seen as fundamental to the analysis of its implementation and the development of this public policy, in order to contribute to the provision of this type of education in the institution. The process of implementation of this mode of education in UNIPAMPA began in 2016, and is gradually being extended. This is started by the accreditation and offer courses in institutional poles and subsequently, through the Open University of Brazil (UAB), in poles of classroom support of Rio Grande do Sul, the latter won by means of an agreement signed between the University and the Open University of Brazil - (UAB). So it is essential to know how this modality of teaching was implemented, what are their workflows and processes, and how they can be qualified, these being the objective of the study was performed from bibliographical research, documentary and field. As a result were elaborated: The EaD UNIPAMPA Guide will be available for consultation on the page of the DEaD, in the site at university; the EaD UNIPAMPA agenda, which will be forwarded a copy printed for each pole, and students will be sent by email, for printing and an mobile app to cellular, containing the information listed in the agenda. These results come as a way of contributing to the actors involved in the activities teachers, students and technical of distance education from UNIPAMPA succeed in a practical and simple, obtain information and guidance about the academic processes, since the university doesn’t have compiled guidelines, and that serve as parameters to all those involved in the process.
Keywords: Educação; Educação aberta; Educação a Distância; Universidade Federal do Pampa; Education; Distance Education; CNPQ::CIENCIAS HUMANAS